Digital Reference Services in Academic Libraries: Towards Building a Cooperative Chat Reference Service in Lebanon - Kammourie, Hweida (2020)
This thesis discusses the implementation of a cooperative chat reference service among Lebanese academic libraries to recognize factors that affect its success or it is failure. In order to do so, an extensive literature review related to Digital Reference Services (DRS) in general, and Chat Reference Service (CRS) in particular has been conducted. Moreover, this research surveyed the Lebanese academic landscape to examine the current state of Lebanese universities regarding DRS and to identify academic institutions that are eligible to be part of a Cooperative Chat Reference Service Pilot Project (CCRSPP) with the aim of responding to the main research question: Can we build a cooperative chat service in academic libraries in Lebanon? To answer this question, two focus groups with head librarians, reference librarians and IT were conducted to start planning the CCRSPP among five academic libraries which happened to be all members of the Lebanese Academic Library Consortium to discover its feasibility. As a result, best practices to implement such project were discussed to avoid pitfalls faced during the implementation. The examined chats are divided into two categories:1). Individual (three universities contacted before the pilot project); and 2). Cooperative (between five universities members of LALC). Outcomes from the thesis study could be used as the foundation to design and implement a cooperative chat reference service and to professionally prepare chat reference librarians and ultimately lead to better performance of the service and better satisfaction of users’ information needs, as well as librarians’ job satisfaction.